Artificial intelligence in information systems research: A systematic literature review and research agenda. (October 2021) - Collins, Christopher; Dennehy, Denis; Conboy, Kieran; Mikalef, Patrick
Abstract: AI has received increased attention from the information systems (IS) research community in recent years. There is, however, a growing concern that research on AI could experience a lack of cumulative building of knowledge, which has overshadowed IS research previously. This study addresses this concern, by conducting a systematic literature review of AI research in IS between 2005 and 2020. The search strategy resulted in 1877 studies, of which 98 were identified as primary studies and a synthesise of key themes that are pertinent to this study is presented. In doing so, this study makes important contributions, namely (i) an identification of the current reported business value and contributions of AI, (ii) research and practical implications on the use of AI and (iii) opportunities for future AI research in the form of a research agenda. Highlights: Provides a state-of-the-art of AI research in Information Systems between 2005 and 2020. Identifies the evolution of how AI is defined over a 15-year period. Synthesises and categorises the reported business value of AI. Analysis and categorises the contributions of 55 primary papers.